Elementary Student Engineers: Their Teamwork, Negotiations, and Problem-Solving. (2nd April 2020) - Silva Mangiante, Elaine; Carpenter, Elizabeth; Robichaud, Hayley
Abstract: Get an inside look at the discourse interactions of third- and fourth-grade students as they consider various design proposals to solve an engineering problem and negotiate a group decision. The authors present possible factors that impact student teamwork and provide recommendations for teachers to develop students' skills for group engineering decision-making.